Global macroeconomic capacity building program: Strengthening BPS Papua staff’s awareness of safe haven and trade war implications for the regional economy - Irianto, Okto; Hapsara, Cendana Murti Nuryana Sri; Bano, Rafly Parenta; Asmaningrum, Henie Poerwandar (Nur Science Institute, 2025)
This community service program aimed to enhance BPS Papua staff's awareness of global macroeconomic dynamics, specifically US-China trade war and safe haven phenomena impacts on regional economy. The program utilized survey method by virtual socialization using Zoom Workplace as platform on April 25, 2025, involving 96 participants from BPS Papua region including structural officials, heads of regencies/cities, functional statistical staff, and KPPN Merauke representatives in a 3-hour session consisting a 2-hour interactive presentation and a 1-hour open discussion. Evaluation was conducted through direct interviews and participation analysis. Results showed excellent engagement with 97% attendance rate, 23 questions during presentations, and 65 discussion contributions, indicating strong material relevance. Post-event interviews with 93 participants revealed 92% found the material highly beneficial for understanding global economic dynamics, with 89% confident in applying knowledge to routine data analysis. This initiative successfully demonstrated virtual learning effectiveness for capacity building in geographically challenging regions while establishing sustainable collaboration between Universitas Musamus and BPS Papua.